Highly Strained Tricyclic Oxanorbornenes with Uncommon Reactivity Enable Rapid ROMP for Thermally High-Performing Polyenes - Grabbet, Björn; Taiem, Abdullah; Cioc, Răzvan C; Bruijnincx, Pieter C A; Thevenon, Arnaud (Macromolecules, 2025)
Bioderived monomers, readily available from biomass via atom- and redox-efficient processes, will need to play a major role in the development of sustainable polymeric materials. Here, we show that a family of tricyclic monomers, efficiently made from biobased furans via Diels-Alder chemistry, allows the production of polyenes with diverse thermo/physical properties through ring opening metathesis polymerization (ROMP). Via small structural variations, we offer insight into the intricacies of monomer design and its implications for polymerization. Notably, the thermostable polyenes all show very similar head-to-tail regioregularities, -linkage isomerism distributions, and narrow dispersities. Additionally, the monomers exhibit rare reactivity with ethyl vinyl ether, which can be used as a chain transfer agent, enabling the synthesis of monotelechelic polyenes. The monomers do differ substantially in polymerization rate, spanning two orders of magnitude, in the extent of molecular weight control and in the properties of the resulting amorphous polymers. With glass transition temperatures ranging from 116 to 217 °C and degradation temperatures exceeding 350 °C, these materials are among the highest performing biobased homopolymers reported. We elucidate these variations, demonstrating that the ROMP is profoundly influenced by subtle structural changes in the monomers.